2022
DOI: 10.1039/d2qo00041e
|View full text |Cite
|
Sign up to set email alerts
|

Amine-directed Mizoroki–Heck arylation of free allylamines

Abstract: The transition metal-catalyzed Mizoroki−Heck reaction is a powerful method to synthesize C–C bonds, allowing access to several important pharmaceuticals. Traditionally free amines have not been compatible with these approaches due...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 95 publications
0
7
0
Order By: Relevance
“…In previous work we had demonstrated that simple allylamine could be diarylated, 7 but monoarylation required milder conditions and increased amine substrate relative to the coupling partner. 9 With this in mind, we looked at the selectivity for mono versus di arylation as a function of the ratio of amine : aryl boronic acid (Scheme 4b). While the monoarylation product was observed almost exclussively when less than 2.5 equivalents of aryl boronic acid were used, further increase in the relative amount of boronic acid could push the reaction to be selective for diarylation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous work we had demonstrated that simple allylamine could be diarylated, 7 but monoarylation required milder conditions and increased amine substrate relative to the coupling partner. 9 With this in mind, we looked at the selectivity for mono versus di arylation as a function of the ratio of amine : aryl boronic acid (Scheme 4b). While the monoarylation product was observed almost exclussively when less than 2.5 equivalents of aryl boronic acid were used, further increase in the relative amount of boronic acid could push the reaction to be selective for diarylation.…”
Section: Resultsmentioning
confidence: 99%
“…Using this approach, a double Heck reaction 8 as well as a selective monoarylation of unprotected allylamines were also reported. 9 All of these reports made use of aryl iodides as coupling partners, and subsequently required the use of Ag salts. 10 Interestingly, although nanoparticles in these reports were judged to be more reactive, there was evidence of background C–H activation by homogeneous Pd II which eroded the E : Z selectivity of the arylation reaction due to the stereospecific nature of each pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Progress in this context was recently, achieved by the Young group who reported the direct Heck reaction of allylamine with aryl iodides in TFA/CO 2 (Scheme 2a). [25] Appa-rently, the latter solvent system provides a means for the in situ and reversible protection of the amine substrate in its carbamic acid form, ultimately participating in the Heck reaction and leading to the isolation of cinnamylamine as its TFA salt. Notwithstanding the merit of the chromatography-free aspect, as with the previous methodologies, the use of silver salts, high palladium loading and TFA as the solvent, render this approach economically unviable for large scale applications.…”
Section: Introductionmentioning
confidence: 99%
“…All protocols described above require column chromatography for the isolation of the pure cinamylamines. Progress in this context was recently, achieved by the Young group who reported the direct Heck reaction of allylamine with aryl iodides in TFA/CO 2 (Scheme 2a) [25] . Apparently, the latter solvent system provides a means for the in situ and reversible protection of the amine substrate in its carbamic acid form, ultimately participating in the Heck reaction and leading to the isolation of cinnamylamine as its TFA salt.…”
Section: Introductionmentioning
confidence: 99%
“…2) The amine 6 was prepared using a modified strategy starting from piperonyl alcohol 1. 32 Compound 1 was oxidized to aldehyde using 2,3-dicholro-5,6-dicyno-1,4-benzoquinone (DDQ) to obtain compound 2 with 90% yield. 33 The aldehyde 2 was subjected to Wittig reaction using ethyl bromoacetate in saturated NaHCO 3 to produce α, β-unsaturated ester 3 in 70% yield.…”
Section: ■ Introductionmentioning
confidence: 99%